Karakterisasi Arang dan Gas-gas Hasil Pirolisis Limbah Kelapa Sawit - Muhammad Raju; Armansyah Halomoan Tambunan; Radite Praeko Agus Setiawan (PERTETA, 2016)
AbstractEmpty fruit bunch (EFB) and shell of oil palm are potential sources of bioenergy because they contain lignocellulose (cellulose, hemycellulose and lignin) which can be converted to bio-oil (liquid), char, or combustible gases by pyrolysis process. Operating temperature of the pyrolysis process will influence the composition of the liquid, char and gases, as well as its characteristics. The objective of this study is to characterize the pyrolysis product of both empty fruit bunch and shell as affected by the pyrolysis temperature. The experiment was conducted by using a lab scale pyrolysis reactor, specially designed with controlable temperature. The temperature of the pyrolysis process was controled at 300°C, 400°C, 500°C, and 600°C level, and the product was measured and analysed. The result showed that pyrolysis of shell produced char, liquid and gases at the range of 34.99 - 63.78%, 22.76 - 43.28% and 13.47 - 21.73%, in mass fraction respectively. While pyrolysis of empty fruit bunch produced char, liquid and gases at the range of 30.66 - 64.7%, 16.25 - 29.16% and 18.98 - 44.49%, in mass fraction respectively. Increasing temperature resulted in increasing calorific value of the pyrolysis char from shell and empty fruit bunch in range of 25.64 – 29.60 kJ/g and 24.50 – 27.86 kJ/g, respectively. However, the calorific value of pyrolysis gases was decreasing with the increasing temperature in range of 12.18 kJ/g – 20.05 kJ/g and 11.98 kJ/g – 15.94 kJ/g, respectively. The gas calorific value did not account H2 gas, which might be the cause of the phenomenon. Shell pyrolysis temperature increasing caused the increasing of CO concentration in range 2.86% - 18.42% while the CH4 concentration increased at 400°C level afterwards decreased at higher temperature level in range of 0.89% - 2.84%. The increasing of EFB pyrolysis temperature increased CO dan CH4 concentration in range 3.8% - 15.74% and 0.29% - 0.76%, respectively.AbstrakCangkang dan tandan kosong kelapa sawit (TKKS) merupakan sumber bioenergi yang potensial karena mengandung lignoselulosa (selulosa, hemiselulosa dan lignin) sehingga dapat dikonversi menjadi cairan, arang atau gas mampu bakar melalui proses pirolisis. Suhu pengoperasian pada proses pirolisis akan mempengaruhi komposisi cairan, arang dan gas serta karakteristik hasil pirolisis tersebut. Tujuan dari penelitian ini adalah untuk mengkarakterisasi produk pirolisis cangkang dan tandan kelapa sawit yang dipengaruhi oleh suhu pirolisis. Penelitian dilakukan dengan menggunakan reaktor pirolisis skala lab, yang didesain khusus agar suhunya dapat dikendalikan. Suhu pirolisis dikendalikan pada level 300°C, 400°C, 500°C dan 600°C, kemudian hasil pirolisis diukur dan dianalisa. Hasil penelitian menunjukkan bahwa pirolisis cangkang menghasilkan fraksi massa arang , cairan dan gas dalam rentang 34.99 - 63.78%, 22.76 - 43.28% dan 13.47 - 21.73% secara berturut-turut. Sedangkan pirolisis TKKS menghasilkan fraksi massa arang, cairan dan gas dalam rentang 30.66 – 64.76%, 16.25 – 29.16% dan 18.98 – 44.49% secara berturut-turut. Peningkatan suhu menghasilkan peningkatan nilai kalor arang hasil pirolisis cangkang dan TKKS dengan rentang antara 25.64 – 29.60 kJ/g dan 24.50 – 27.86 kJ/g. Tetapi, nilai kalor gas pirolisis menurun seiring dengan peningkatan suhu pirolisis dengan rentang 12.18 kJ/g – 20.05 kJ/g dan 11.98 kJ/g – 15.94 kJ/g untuk pirolisis cangkang dan TKKS. Nilai kalor gas tidak menghitung gas H2 yang mungkin menyebabkan fenomena tersebut. Peningkatan suhu pirolisis cangkang kelapa sawit mengakibatkan peningkatan konsentrasi gas CO pada rentang 2.8% - 18.42% sementara konsentrasi gas CH4 meningkat pada suhu 400°C namun menurun kembali dengan rentang 0.89% - 2.84%. Peningkatan suhu pirolisis TKKS meningkatkan konsentrasi gas CO dan CH4 pada rentang 3.81% - 15.74% dan 0.29% - 0.76%.